Sulfated zirconia; an efficient and reusable acid catalyst for the selective synthesis of 4-phenyl-1,3-dioxane by Prins cyclization of styrene - Marakatti, Vijaykumar S.; Shanbhag, Ganapati V.; Halgeri, A.B. (Applied catalysis. A, General, 2013)
Prins cyclization of styrene with paraformaldehyde was carried out over sulfated zirconia (SZ) catalyst in liquid phase. The SZ catalysts were synthesized by precipitation method with different sulfur impregnation and characterized by XRD, FT-IR, Nitrogen sorption, NH3-TPD. The SZ showed best performance among different types of acid catalysts. The acidity of SZ optimized by different concentrations of H2SO4 treatment influences the selectivity for dioxane. The sulfur loading, nature of solvent, temperature, catalyst amount, mole ratio and reusability of catalyst were investigated. The SZ catalyst synthesized by impregnating 2N sulfuric acid was found to be highly selective for the synthesis of 4-phenyl-1,3-dioxane (93%) with almost complete conversion of styrene ( similar to 100%). The catalyst was recycled thrice with negligible decrease in the yield of 4-phenyl-1,3-dioxane.